2023
DOI: 10.7759/cureus.48309
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Perception Regarding Artificial Intelligence in Periodontology: A Questionnaire Study

Ruhee L Chawla,
Nidhi P Gadge,
Sunil Ronad
et al.

Abstract: Introduction: The utilization of artificial intelligence (AI) and machine learning (ML) models has brought about a significant transformation in the manner in which periodontists gather information, evaluate associated risks, develop diverse treatment alternatives, anticipate and diagnose dental conditions that compromise periodontal health. The principal objective of this prospective study was to examine periodontists’ understanding and acceptance of the application of AI in the realm of periodontology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The importance of clinical findings, especially in the diagnosis of disease in the periodontal area, reinforces this situation. However, it would be beneficial to integrate AI into regular training programs to increase both the development and motivation of periodontists [13]. The reported lack of awareness of AI in dentistry may confirm this need [14].…”
mentioning
confidence: 99%
“…The importance of clinical findings, especially in the diagnosis of disease in the periodontal area, reinforces this situation. However, it would be beneficial to integrate AI into regular training programs to increase both the development and motivation of periodontists [13]. The reported lack of awareness of AI in dentistry may confirm this need [14].…”
mentioning
confidence: 99%
“…A recent study showed that only 68% of periodontists were aware of AI but only 24% were aware of its working principle. 8 So, AI has still a long way to go in the field of periodontology and oral implantology. However, the accuracy in diagnosis and treatment planning that AI brings can never be neglected and should be used whenever possible and feasible for the benefit of both periodontist and their patient.…”
mentioning
confidence: 99%